Islamic of Psychology: A Literature Review Understanding the Concept of Religious Moderation Among Students at University - Muhamad Uyun (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research aims to examine the important role of the Islamic psychology approach in strengthening religious moderation in university students. The method used in this research is a literature study that involves analysis of various scientific references that discuss the topic of religious moderation and Islamic psychological approaches. The main references used come from journals and books that have been published by experts in this field. Data was collected through searches in various academic databases using certain keywords. Journal standards and year of publication are also taken into consideration in selecting references. From the literature review, the author identifies that the Islamic psychology approach can make a positive contribution to strengthening religious moderation in students. Students can overcome stress and increase self-resilience through the application of Islamic psychology principles. They can also develop themselves holistically by understanding the role of Islamic-based education in forming moderate character and personality. These findings indicate that the Islamic psychology approach has great potential to help college students strengthen religious moderation. The implication of these findings for education is the need to integrate Islamic psychology approaches into the university curriculum. This article concludes that by applying the principles of Islamic psychology, students can form a balanced character and personality and be able to face various life challenges with strong resilience. The implication is that this approach should be integrated into the higher education climate to form students who are moderate, competitive, and able to have a positive impact on society.